Identification of a Novel Pathogen of Peanut Root Rot, Ceratobasidium sp. AG-A, and the Potential of Selected Bacterial Biocontrol Agents - Ying Li; Xia Zhang; Xinying Song; Manlin Xu; Kang He; Yucheng Chi; Zhiqing Guo (Journal of Fungi)
Peanut root rot poses a significant threat to global peanut production. In order to identify the new pathogen of peanut root rot in Shandong province, China, and to screen the effective antagonistic biocontrol strains against the identified pathogen, ten symptomatic plants from a peanut field (10% disease incidence) of Rongcheng were sampled for pathogen isolation. The predominant isolate RC-103 was identified as Ceratobasidium sp. AG-A through morphological characterization and phylogenetic analysis of ITS and RPB2 sequences. Pathogenicity was confirmed via Koch’s postulates. Three potent biocontrol strains, namely Bacillus subtilis LY-1, Bacillus velezensis ZHX-7, and Burkholderia cepacia Bc-HN1, were screened for effective antagonism against isolate RC-103 by dual-culture analysis. Their cell suspensions could significantly inhibit the hyphal growth of isolate RC-103, with the percentage inhibition of 54.70%, 45.86%, and 48.62%, respectively. Notably, the percentage inhibition of 10% concentration of the cell-free culture filtrate of B. subtilis LY-1 was as high as 59.01%, and the inhibition rate of volatile organic compounds of B. cepacia Bc-HN1 was 48.62%. Antagonistic mechanisms primarily involved the induction of hyphal abnormalities. In addition, the culture filtrate of these biocontrol bacteria significantly promoted the growth of peanut and increased the resistance of peanut plants to isolate RC-103, with the biocontrol efficiency reaching 41.86%. In summary, this study identified a novel pathogen of peanut root rot, Ceratobasidium sp. AG-A, which was reported for the first time in China, and screened three highly effective antagonistic biocontrol strains against Ceratobasidium sp. AG-A isolate RC-103, providing the scientific basis to study the epidemiology and management of this disease.